2022
DOI: 10.1002/ggn2.202100056
|View full text |Cite
|
Sign up to set email alerts
|

Social Determinants of Health Factors for Gene–Environment COVID‐19 Research: Challenges and Opportunities

Abstract: The characteristics of a person's health status are often guided by how they live, grow, learn, their genetics, as well as their access to health care. Yet, all too often, studies examining the relationship between social determinants of health (behavioral, sociocultural, and physical environmental factors), the role of demographics, and health outcomes poorly represent these relationships, leading to misinterpretations, limited study reproducibility, and datasets with limited representativeness and secondary … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 113 publications
0
7
0
Order By: Relevance
“…Furthermore, in the context of dementia, a previous study suggested that accounting for socioeconomic factors such as income and formal education level may mitigate differences in dementia incidence between Black- and White- identified individuals 47 . There are a number of challenges obtaining individual-level SDoH in the EMR 48 , including the lack of systematic inclusion. However, several community-level SDoH can be assessed for patients with known addresses, including median income, food access 49 , and environmental pollution 50 , though using these broader SDoH indicators to describe individuals have important limitations 51 .…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, in the context of dementia, a previous study suggested that accounting for socioeconomic factors such as income and formal education level may mitigate differences in dementia incidence between Black- and White- identified individuals 47 . There are a number of challenges obtaining individual-level SDoH in the EMR 48 , including the lack of systematic inclusion. However, several community-level SDoH can be assessed for patients with known addresses, including median income, food access 49 , and environmental pollution 50 , though using these broader SDoH indicators to describe individuals have important limitations 51 .…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, in the context of dementia, a previous study suggested that accounting for socioeconomic factors such as income and formal education level may mitigate differences in dementia incidence between Black-and Whiteidentified individuals 37 . While there are current challenges to identifying individual-level SDoH in the EMR 38 , several community-level SDoH can be assessed for patients with known addresses, including median income, food access 39 , and environmental pollution 40 , though using these broader SDoH indicators to describe individuals have important limitations 41 . We plan to identify strategies to properly incorporate SDoH in future work.…”
Section: Discussionmentioning
confidence: 99%
“…For example, doses for the drug warfarin, a blood-thinning drug, have been reported as being prescribed based on an individual’s race and ethnicity, despite genetic studies mainly being conducted on European and white Americans 31. There is also evidence to suggest that there is some misunderstanding among biomedical researchers around the differences between sociopolitical constructs like race and ethnicity and biological factors such as genetic ancestry, which can lead to estimates of genetic heredity being biased if environmental and social determinants of health are taken into consideration during analysis 33. Enabling representation of people from BAFDC in health and care research is critical for innovation and new discoveries; data science; ensuring access to specific therapeutic drugs, or treatments; building trust in science and medicine; addressing health disparities and ensuring provision of evidence-based healthcare 14 34.…”
Section: Introductionmentioning
confidence: 99%
“… 31 There is also evidence to suggest that there is some misunderstanding among biomedical researchers around the differences between sociopolitical constructs like race and ethnicity and biological factors such as genetic ancestry, which can lead to estimates of genetic heredity being biased if environmental and social determinants of health are taken into consideration during analysis. 33 Enabling representation of people from BAFDC in health and care research is critical for innovation and new discoveries; data science; ensuring access to specific therapeutic drugs, or treatments; building trust in science and medicine; addressing health disparities and ensuring provision of evidence-based healthcare. 14 34 Without this, there is a risk of perpetuating health inequalities and social injustice with data producing algorithms used to guide treatment decisions based on White populations.…”
Section: Introductionmentioning
confidence: 99%